Open-Ended Approach for Critical Thinking Skills in Mathematics Education: A Meta-Analysis - Yuni Fitriyah; Wahyudin; Suhendra; Hanifah Nurhayati; Tri Sedya Febrianti (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2024)
There have been numerous research on developing students’ critical thinking skills through an open-ended approach in mathematics education show conflicting results. Some research results implied a strong effect; others range from moderate to modest effect. This research aims to summarize and predict the implementation of an open-ended approach to critical thinking skills in mathematics education over the last five years. This research utilized a meta-analysis using the PICOS (Population, Interventions, Comparator, Outcomes, and Study Design) approach. The sample used in this research is studies published in the form of articles and proceedings as well as theses and dissertations. The databases are sourced from Google Scholar, Crossref, and Semantic Science using the PRISMA (Preferred Reporting Items for Systematic Review and Meta-Analyses) method, which includes 14 primary studies found during 2018-2023 in Indonesia. The results are the implementations of an open-ended approach to improve critical thinking skills in mathematics education, show an average of 1.44, which is included in the high category. Factors that influence the heterogeneity of effect sizes are study characteristics, such as sample size, year of publication, level of education, demographics, and publication type. The characteristics of the research that results in a large effect size value are an open-ended approach implemented in elementary schools, studies with a sample size of more than 30, studies that are published in 2018 and in journals, and implementation of the approach in regencies.